Diagnosis and Management of Femoroacetabular Impingement : An Evidence-Based Approach - Ayeni, Olufemi R.; Karlsson, Jón; Philippon, Marc J.; Safran, Marc R. (Springer International Publishing : Imprint: Springer, 2017)
This book is unique in combining an exclusive focus on femoroacetabular impingement (FAI) with an evidence-based approach and the involvement of a diverse group of global experts. It is designed to meet the worldwide need for a summary of current evidence that will readily assist the physician in establishing the most accurate diagnosis and providing the best available treatment. The coverage is wide ranging, encompassing clinical examination, differential diagnosis, imaging, indications for surgery, contemporary arthroscopic and open management, treatment of labial tears, cartilage injury management, non-operative management, rehabilitation, treatment of complications, and revision surgery. Trainees, physicians, surgeons, and allied health care professionals who treat young adults with hip pain will find the book to be an excellent source of information on what procedures are most helpful and how they should be implemented.
Keywords: Medicine.; Orthopedics.; Primary care (Medicine).; Sports medicine.; elektronické knihy; electronic books